The Dynamics of the Ingkung Suran Tradition in Marriages among Kuwarisan Descendants in Kebumen: An Analysis of Cultural Acculturation and ‘Urf - Sabilla Pre Eklamsianingrum (QURU’: Journal of Family Law and Culture, 2026)
The Ingkung Suran tradition in Kuwarisan, Kebumen represents a sustained local cultural practice, particularly among individuals who marry into families of Kuwarisan descent. This tradition reflects a complex interplay between Javanese culture, Islamic values, kinship systems, and customary legal practices within a local Muslim society. This study aims to analyze the relationship between cultural acculturation, cultural assimilation, and the concept of ‘urf in Islamic law within the practice of the Ingkung Suran tradition. This research employs a field research design with a descriptive-qualitative approach and a socio-religious perspective. Data were collected through observation, in-depth interviews with community leaders and participants, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the Ingkung Suran tradition embodies a process of cultural acculturation, where Javanese cultural elements are maintained while being reinterpreted through Islamic meanings, such as the symbolism of submission to God and collective prayer. In the context of marriage, the tradition also reflects cultural assimilation, as non-Kuwarisan spouses integrate into the local kinship and cultural system. From the perspective of ‘urf, this tradition can be categorized as ‘urf ṣaḥīḥ, as it contains socio-religious benefits and does not contradict Islamic principles, provided it is not regarded as a religious obligation. This study contributes to the discourse on Islam Nusantara by demonstrating how local traditions, marriage, and Islamic law dynamically interact within contemporary Muslim communities.